2020
DOI: 10.1183/13993003.01123-2020
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression andin situprotein profiling of candidate SARS-CoV-2 receptors in human airway epithelial cells and lung tissue

Abstract: In December 2019, SARS-CoV-2 emerged causing the COVID-19 pandemic. SARS-CoV, the agent responsible for the 2003 SARS outbreak, utilises ACE2 and TMPRSS2 host molecules for viral entry. ACE2 and TMPRSS2 have recently been implicated in SARS-CoV-2 viral infection. Additional host molecules including ADAM17, cathepsin L, CD147, and GRP78 may also function as receptors for SARS-CoV-2.To determine the expression and in situ localisation of candidate SARS-CoV-2 receptors in the respiratory mucosa, we analysed gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 71 publications
9
115
0
1
Order By: Relevance
“…Zhang et al 6 assessed the ACE2 gene expression in NS and smokers. Consistently with theirs and others' findings 5,6,10 , we found ACE2 expression to be higher in central airways. While Zhang et al did not include COPD patients in their analyses, Cai et al 5 and Smith et al 9 analyzed several datasets of gene expression of COPD and control small and large airway epithelium samples, concluding that ever-smoking was the main factor associated with high ACE2 levels;…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Zhang et al 6 assessed the ACE2 gene expression in NS and smokers. Consistently with theirs and others' findings 5,6,10 , we found ACE2 expression to be higher in central airways. While Zhang et al did not include COPD patients in their analyses, Cai et al 5 and Smith et al 9 analyzed several datasets of gene expression of COPD and control small and large airway epithelium samples, concluding that ever-smoking was the main factor associated with high ACE2 levels;…”
Section: Resultssupporting
confidence: 93%
“…ACE2 expression is highest in the conducting airways, waning in the more distal bronchiolar and alveolar lung regions 3 . There have been mixed reports on the effect of CS and COPD on SARS-CoV-2 infection 4 , with most studies showing an up-regulation of ACE2 in clinical and experimental models of smoke-induced lung disease [5][6][7][8][9][10] . In this study, we evaluated: 1) ACE2 and TMPRSS2 expression in the airways of smokers with COPD, compared to smoker and never smoker (NS) controls, and 2) ACE2 expression in lungs of mice acutely and chronically exposed to CS; and 3) the effect of CS on SARS-CoV2 infection of bronchial epithelial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…This mode of infection may contribute to vascular pathology and thrombosis in COVID-19 patients [85,86]. Also, two other proteins CD147 and GRP78 were recently reported to aid in cell entry in the respiratory mucosa [87].…”
Section: Organotropismmentioning
confidence: 95%
“…[18][19][20][21][22][23][41][42][43] However, multiple studies have shown no differences between males and females in ACE2 and TMPRSS2 mRNA or protein expression in human or murine lung tissue, indicating that T is unlikely to upregulate these gene products in lung, [44][45][46][47][48][49] using a microarray gene expression data set generated from bronchial brushings of 504 healthy subjects reported that gender did not correlate with gene expression of any candidate host molecule involved in COVID-19 infection, and that ACE2 and TMPRSS2 were the lowest expressed genes of interest among those examined. 49 The authors suggested that alternative mechanisms in the respiratory mucosa may become important during COVID-19 infection, perhaps including other coreceptors. Similarly, Asselta et al 50 found no significant evidence that ACE2 or TMPRSS2 are associated with disease severity/gender disparity in the Italian population.…”
Section: Deaths In Different States Within the United Statesmentioning
confidence: 99%